Parental time from the perspective of time pressure: The idea of intensive parenting (Szociológiai Szemle, 2023)
While there is an upward trend in the time parents and children spend together, there is also intensifying parental anxiety about whether they are spending enough and sufficient quality time with children. The significant impact of parental time on children’s cognitive and social outcomes and wellbeing is well documented in the literature. This importance is also reflected in the often-used notion of quality time in academic and public debate, which emphasizes the nature of parental time. Moreover, there is growing evidence that a ‘squeezed’ feeling of time characterizes the lives of contemporary families. The difficulties of reconciling work and family life mostly concern parents. This paper reviews the literature about parental time based on the problem of time pressure, and related to this, the paradoxical anxiety of today’s parents about the time they devote to their children. The article aims to describe parenting trends and focuses on parental time by exploring its features and influential factors.First, we review the characteristics of changing expectations about parenthood and discuss emerging concepts concerning the time parents and children spend together related to the ideals of contemporary parenting. Second, based on earlier empirical findings, the most important factors are outlined and elaborated. Reflecting on the Hungarian context, related findings are also presented.